Multi-scale evaluation of the linear elastic and failure parameters of the unidirectional laminated textiles with application to transverse impact simulation. (10th May 2016) - Calneryte, D.; Barauskas, R.
Abstract: Unidirectional laminated textiles (UDLTs) are flexible non-crimped fabric structures, the UD layers of which are bonded together by small amounts of thermoplastic resin and covered by polyethylene films over their external surfaces. Applications of them in ballistic protection clothes ensure lesser costs and ability to resist the penetration of humidity, which may substantially decrease the overall ballistic strength of the structure. This research focuses on the hierarchical multi-scale approach formulated for large displacement, material non-linearity and failure. The micro-scale model of UDLT represents matrix and fibres by means of 3D solid elements. A representative small volume (micro-cube) of the UDLT composite is subjected to a series of large deformation tests up to the failure, which enable to approximately evaluate linear elastic and failure parameters of the orthotropic shell elements that represent the mechanical behaviour of UDLT at rougher scale. Obtained longitudinal, transversal and shear strength parameters in association with the corresponding strains are the parameters used at mezzo-scale in order to calculate the Hashin criteria for the shell element failure. The results of the research are employed in order to achieve reasonable computational costs during the simulation of ballistic penetration through multi-layer UD composite textile structures at medium velocity range.